Impactos da idéia de pobre e de pobreza na institucionalização de crianças e adolescentes em regime de abrigamento - Mendes, Mario César Torres [UNESP] (2015)
From a methodological point of view, this theme shouldn‟t be developed on a reductional and compartmentalized perspective, pointing only it‟s juridical or institutional aspects. In face of the necessity of establish a better understanding about the enigmatic and obscure models of vulnerable population caring, (as natural consequences of a new problematization of legal and institutional poor childhood caring mechanisms, brought by our country‟s democratization), this thesis has the goal of establish a general panorama of the characteristics and conditions of shelter institutions, starting by its historical background, aiming to discuss the social, political and juridical nature of public policies related to childhood shelters. For that goal, we intend to compare the legislation content with the practices of the public agents. In this paper, we will seek to establish, through the exploration of a big amount of quantitative data worked mainly by IPEA, the central characteristics of the children shelter institutions. Keeping in mind who are the children who have previously been in institutionalized care., and the reasons for this, we will analyze the documentation produced by many researchers that gave voice for the children, as well as for the administrative and control agents from the institutions.